Molly's game [videorecording (DVD)] - Sorkin, Aaron; Chastain, Jessica, 1977-; Elba, Idris; Costner, Kevin; Cera, Michael; Bloom, Molly (Universal Pictures Home Entertainment, 2018)
The true story of Molly Bloom, an Olympic-class skier who ran the world's most exclusive high-stakes poker game and became an FBI target.